Africa: State, drivers, responses, and challenges - Ulimwengu, John M.; Mawia, Harriet (2023)
John Ulimwengu and Harriet Mawia GLOBAL FOOD POLICY REPORT IFPRI’s 2023 Global Food Policy Report: Rethinking Food Crisis Responses – Considerations for Africa IFPRI Africa Regional Office JUN 22, 2023 - 9:00 TO 10:30AM EDT